Surgical correction of ureter rupture due to stenosis induced secondary to accidental injury by placing nephrovesical subcutaneous ureteric bypass in a dog - Choi, Gab-Chol; Jeong, In-Seong; Seo, Beom-Seok; Lee, Gi-Jong; Kim, Young Hwan; Rahman, Md. Mahbubur; Kim, Sehoon (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The aim of this paper is to report surgical correction of ureteric rupture due to stenosis induced secondary to accidental injury by placing nephrovesical subcutaneous ureteric bypass in a dog and postoperative long term outcomes. Materials and methods: Imaging techniques revealed multiple bone fractures as well as left proximal ureter injury. The all bone fractures were corrected using standard techniques while left proximal ureter injury was treated as conservation medical therapy. One month later, contrast media were also found in proximal ureter and abdomen which indicated ureter rupture. This rupture was corrected surgically by nephrovesical subcutaneous ureteric bypass (SUB) under fluoroscopy guidance. Results: First day after accidental injury, the serum BUN and CRE were 10.7 mg/dL and 0.9 mg/dL, respectively which indicated kidney injury but by conservative therapy these parameters were lowered gradually. On the 5th day after considering these parameters, the dog was judged normal. However, on the 31st day BUN and CRE were 14.3 mg/dL and 0.8 mg/Kg, respectively. The Doppler ultrasonography revealed hydroneprosis, proximal ureter stenosis and high resistive index (0.72±0.02) in the renal arcuate artery indicating renal abnormalities due to ureter obstruction. On re-examination by radiography after one month postoperatively, revealed that patency of the device and normal renal function. The dog was clinically normal with normal urination and no complications were found 6 months postoperatively. Conclusion: In view of the above findings, it is suggested that the SUB system can be a better alternative to preserve the kidney in non-reparable traumatic ureteral damage in dogs. http://doi.org/10.5455/javar.2018.e266